Metacognitive Capacity as a Predictor of Insight in First-Episode Psychosis. Issue 5 (May 2015) - Vohs, Jenifer L.; Lysaker, Paul H.; Liffick, Emily; Francis, Michael M.; Leonhardt, Bethany L.; James, Alison; Buck, Kelly D.; Hamm, Jay A.; Minor, Kyle S.; Mehdiyoun, Nikki; Breier, Alan
Abstract : Abstract: Impaired insight is common in the first episode of psychosis (FEP). Although considerable research has examined the factors that are associated with impaired insight in chronic psychosis, less is known about the factors that underlie and sustain poor insight in FEP. Impaired metacognition, or the ability to form integrated representations of self and others, is a promising potential contributor to poor insight in FEP. To explore this possibility, the authors assessed insight and metacognition in 40 individuals with FEP and then examined the relationship between these areas and social cognition domains, neurocognitive domains, and psychotic symptoms. Correlation analyses revealed that improved insight was associated with higher metacognition, better vocabulary and Theory of Mind scores, and fewer symptoms. The domain of metacognitive mastery also predicted clinical insight. Results support the need to develop an integrative therapeutic approach focused on improving metacognition, hence addressing poor insight in FEP.